Role of Information Technology in Shaping National Economy - Dr. Shalini Kapur; Dr. Anjali Srivastav (International Journal of Engineering and Management Research, 2022)
India's economy is as diversified as it is huge, with manufacturing industries, agriculture, textiles and handicrafts, and services among its major sectors. Agriculture is an important part of the Indian economy, with almost 66 percent of the population relying on it for a living. The service industry, on the other hand, is rapidly developing and has begun to play an increasingly important role. Because India's Indian-speaking population is expanding by the day, it has become a centre for outsourcing activities for some of the world's most powerful economies, like the United Kingdom and the United States. Technical assistance and customer service have been the most common areas of outsourcing to India. Recent trends have seen India exporting the services of a numerous information technology (IT) professionals. IT professionals have been sought for their expertise in software, software engineering and other financial services This has been possible as a result of the high skill levels of Indian IT professionals.